Immunomodulation by bacterial products promotes innate signatures favorable to macrophage responses in tuberculosis infection - Romero-Rodríguez, Dámaris P.; Montes, Eduardo; Rocha-González, Héctor Isaac; Torres, Martha; Zúñiga, Joaquín; Juárez, Esmeralda (Frontiers in Immunology, 2025)
BackgroundTuberculosis remains a leading cause of death from infectious diseases globally, underscoring the need to boost innate responses in monocytes and macrophages to enhance early control of Mycobacterium tuberculosis infection. Trained immunity, a form of innate immune memory, enhances macrophage responsiveness through epigenet ic and metabolic reprogramming, offering a promising approach to strengthen host defenses against M. tuberculosis.MethodsThis study evaluated the immunomodulatory potential of pharmaceutical-grade bacterial suspension (BS) and bacterial lysates (BL) in human monocyte-derived macrophages (MDM) and their role in innate response to M. tuberculosis infection. MDMs were stimulated with M. bovis BCG, BS, and BL following a training protocol described for BCG-dependent trained immunity.ResultsWe observed that BS and BL induced sustained cytokine responses and a metabolic transcriptional profile upon secondary stimulation with M. tuberculosis. BS and BL promoted increased IL-1b production in M. tuberculosis-infected MDMs. Additionally, the expression of surface markers shifted to high levels of CD80, CD86, HLA-DR, TLR2, and CD16 and low expression of CD163, TLR9, CCR2, and TLR4, consistent with an M1 phenotype. Moreover, BS and BL upregulated antimicrobial transcriptional signatures, including autophagy-related MAP1LC3 and ATG16L1.DiscussionThese findings indicate that BS and BL engage training-associated transcriptional and phenotypic changes, providing new adjunctive strategies to boost innate responses in tuberculosis and other chronic infections.